2021
DOI: 10.1021/acsenergylett.1c02011
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer Triplet-Sensitized Luminescence in Layered Two-Dimensional Hybrid Metal-Halide Perovskites

Abstract: Here we review an emerging class of 2D layered metal-halide perovskites that exhibit important photophysical behavior involving inorganic exciton-to-molecular triplet energy flow. These novel systems have potential to impact several energy-related fields and processes, including optoelectronics, photon upconversion strategies, and triplet-based photocatalysis. Early studies provided initial guidance and revealed several intriguing questions that more recent developments, in terms of both expanded and diversifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 148 publications
1
30
0
Order By: Relevance
“…Whereas the S 1 level of the organic spacer located above the E x prohibits the energy transfer from inorganic to organic components. [ 14 ] Once this energy transfer process occurs, the organic spacer rapidly relaxes to the minimum of potential energy surface of the triplet states, leading to a lower T 1 * excitation energy. The T 1 * excitation energy corresponds to the lowest emission peak of the phosphorescence, and it is an important design parameter for RTP materials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas the S 1 level of the organic spacer located above the E x prohibits the energy transfer from inorganic to organic components. [ 14 ] Once this energy transfer process occurs, the organic spacer rapidly relaxes to the minimum of potential energy surface of the triplet states, leading to a lower T 1 * excitation energy. The T 1 * excitation energy corresponds to the lowest emission peak of the phosphorescence, and it is an important design parameter for RTP materials.…”
Section: Resultsmentioning
confidence: 99%
“…If the triplet energy level of the organic spacers is located below the Wannier exciton level of the perovskite layer, the Dexter-type energy transfer from the inorganic layer to the organic layer may occur. [13,14] Once the energy transfer arises, subsequent recombination of the triplet excitons in the organic spacer layers can lead to the phosphorescence emission. This phenomenon was first reported by Era et al, who observed the strong phosphorescence of the organic spacer in the PbBr-based layer perovskites with naphthalene-linked ammonium molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent development of low-dimensional or two-dimensional (2D) halide perovskites offers an additional route to efficiently sensitize molecular triplets . 2D perovskites differ from their three-dimensional (3D) counterparts in that small A-site cations like methylammonium or cesium are replaced by bulky organic spacer cations, which separate the lead halide octahedra in the perovskite lattice. , 2D perovskites thus form an extended multiple quantum-well structure, with intimate contact between the sheets of inorganic lead halide octahedra and the organic cations.…”
Section: Triplet Energy Transfermentioning
confidence: 99%
“…However, movement of triplets within the 2D structure is challenging, and effective extraction of sensitized triplets is an important direction of ongoing research. Although the mechanistic understanding of triplet sensitization in 2D perovskite is still in a relatively nascent stage, it appears that triplet energy transfer proceeds via a Dexter-like two-step mechanism in naphthalene-containing 2D perovskites, similar to that of perovskite nanocrystals. ,,, For further information on 2D perovskites for triplet sensitization, the interested reader is directed to recent reviews. , …”
Section: Triplet Energy Transfermentioning
confidence: 99%